Dampak Budaya Organisasi, Kompetensi dan Motivasi Kerja terhadap Kinerja Guru - Kurroman, M. Taufik; Ilhami, Susanti Dwi (Asatiza: Jurnal Pendidikan, 2024)
This research aims to obtain proof and analysis of the impact of organizational culture, competence and work motivation on teacher performance at AL Mubaarok Rembang Vocational School. The sampling technique applied was a saturated sample of 38 permanent teachers. The type of research is quantitative with data analysis techniques using multiple linear regression analysis. Data collection was carried out by distributing questionnaires. Research findings show that organizational culture and work motivation have a significant positive impact on teacher performance. On the other hand, competence has an insignificant positive impact on teacher performance. Based on the determination test, the resulting Adjusted R Square value is 0.626, which means that the variables of organizational culture, competency and work motivation can explain teacher performance by 62.6%, while the remaining 37.4% of teacher performance is explained by other variables outside the model.